TINJAUAN TENTANG TUGAS DAN TANGGUNG JAWAB ROOM SERVICE WAITER DI HOTEL JW MARRIOTT MEDAN - Ivan Benedict Tambunan (Akademi Pariwisata Darma Agung, 2023)
The purpose of the author's research is to learn about the performance of the duties and responsibilities of the room service waiter, to know the obstacles encountered by the Room Service Waiter, the role of the Supervisor in overcoming obstacles occurring in the implementation of room service Waiter at the JW Marriott Hotel Medan.The method of research used by the author is descriptive, that is, by observing the object of research in person. As for the population data and samples in the study of nine people consisting of three order takers who captured the job as a cashier, three room service waiters, one captain, one supervisor and one food and beverage manager.The author may conclude that in carrying out his duties the room service waiter was less responsible, in the case of delayed delivery of food, he found the obstacles that occurred when night shift and room service waiters were less aware of the menus sold and less fluent in English language, as well as supervised supervisors and managers were less in providing briefing and oversight of the room services waiter before operational work began.